2017
DOI: 10.1017/jpa.2016.158
|View full text |Cite
|
Sign up to set email alerts
|

A diverse assemblage of Permian echinoids (Echinodermata, Echinoidea) and implications for character evolution in early crown group echinoids

Abstract: The Permian is regarded as one of the most crucial intervals during echinoid evolution because crown group echinoids are first widely known from the Permian. New faunas provide important information regarding the diversity of echinoids during this significant interval as well as the morphological characterization of the earliest crown group and latest stem group echinoids. A new fauna from the Capitanian Lamar Member of the Bell Canyon Formation in the Guadalupe Mountains of West Texas comprises at least three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Our analyses also show that stem group and crown group echinoids, which inhabited the same environments in the Permian [ 28 ], must have coexisted from the Roadian, when the first crown group echinoid is known from the fossil record, until at least the Anisian occurrence of Y. luopingensis ( figure 3 a ). This implies an overlap in stratigraphic ranges of approximately 23 Myr between stem group and crown group echinoids ( figure 3 b ), and potentially longer as suggested by disarticulated ossicles [ 7 ].…”
Section: Discussionmentioning
confidence: 73%
“…Our analyses also show that stem group and crown group echinoids, which inhabited the same environments in the Permian [ 28 ], must have coexisted from the Roadian, when the first crown group echinoid is known from the fossil record, until at least the Anisian occurrence of Y. luopingensis ( figure 3 a ). This implies an overlap in stratigraphic ranges of approximately 23 Myr between stem group and crown group echinoids ( figure 3 b ), and potentially longer as suggested by disarticulated ossicles [ 7 ].…”
Section: Discussionmentioning
confidence: 73%
“…Thompson et al . () recently showed that crenulate tubercles are present in a number of Permian archaeocidarids, and that this character probably pre‐dated the origin of the crown‐group echinoids. Given that there are no archaeocidarid species in our analyses from the Permian, however, crenulate primary tubercles are limited to A. apheles and the miocidarids.…”
Section: Methodsmentioning
confidence: 99%
“…The geologically oldest crown group echinoids are the cidaroids of the family Miocidaridae Durham & Melville, , which confidently date to, at the oldest, the Roadian stage of the Permian (Thompson et al . , ). Fossil‐calibrated divergence time estimation analyses also consistently place the origin of the echinoid crown group in the Permian or Carboniferous (Smith et al .…”
Section: The Family Archaeocidaridaementioning
confidence: 99%
“…Reich & Smith ; Thompson & Denayer ; Thompson et al . ; Thompson & Ewin ). A few of these taxa have teeth elements adorally serrated ( Archaeocidaris , Fournierechinus , Hyattechinus , Polytaxicidaris , Proterocidaris ; Reich & Smith ; Thompson & Denayer ; Thompson et al .…”
Section: Linguaserrid Echinoderms: Ophiocistioid Versus Echinoid Teethmentioning
confidence: 99%
“…A few of these taxa have teeth elements adorally serrated ( Archaeocidaris , Fournierechinus , Hyattechinus , Polytaxicidaris , Proterocidaris ; Reich & Smith ; Thompson & Denayer ; Thompson et al . ; Thompson & Ewin ) with a primary point flanked by 2–3 secondary points (cf. Reich & Smith , fig.…”
Section: Linguaserrid Echinoderms: Ophiocistioid Versus Echinoid Teethmentioning
confidence: 99%